(untitled) (Research, Society and Development, 2022)
Objective: to investigate stress levels and quality of life in mothers of children with heart disease. Method: exploratory study with 23 mothers of children with heart disease who answered the Parental Stress Scale: Neonatal Intensive Care Unit (PSS: NICU) and Quality of Life (WHOQOL-BREF) questionnaires. Results: the responses to the WHOQOL-BREF indicated that 17% of the mothers recognized their quality of life as good; 21% like it needs improvement and 60% like it regular. The stress scale in the ICU points out that the areas of the baby’s appearance and behavior and changes in the mother’s role are those that cause the most stress during hospitalization, considering that between 84% and 100% of the answers had the maximum level (level 5) of stress as a prevalent response. Conclusion: This study pointed out some factors that are potentially stressful and can change the quality of life of mothers of children with heart disease: the diagnosis of childhood heart disease, surgeries, hospitalization, initial care that extends into a chronic disease. In addition, it is likely that this affectation is also associated with constituent elements of each parental and family relationship and which are supported by different life stories.